2014
DOI: 10.1371/journal.pone.0091864
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Rumen Microbiome and Residual Feed Intake-Efficiency of Brahman Bulls Stocked on Bermudagrass Pastures

Abstract: Residual feed intake (RFI) testing has increased selection pressure on biological efficiency in cattle. The objective of this study was to assess the association of the rumen microbiome in inefficient, positive RFI (p-RFI) and efficient, negative RFI (n-RFI) Brahman bulls grazing ‘Coastal’ bermudagrass [Cynodondactylon (L.) Pers.]under two levels of forage allowance (high and low stocking intensity). Sixteen Brahman bulls were previously fed in confinement for 70 d to determine the RFI phenotype. Bulls were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 44 publications
13
81
1
Order By: Relevance
“…In other ecosystems, increased biodiversity is associated with greater success and resilience of the ecosystem 10,11 ; however, the data presented in this study suggest that α -diversity may not be a significant contributing factor to feed efficiency phenotypes in stable bacterial communities in growing beef steers. Previous studies have also observed the same relationships between rumen bacterial α -diversity and feed efficiency phenotypes in steers 12,13 . Other factors, such as divergences in individual taxa or functionality of the rumen microbiota, may play a greater role in dictation of host feed efficiency phenotypes.…”
Section: Discussionsupporting
confidence: 73%
“…In other ecosystems, increased biodiversity is associated with greater success and resilience of the ecosystem 10,11 ; however, the data presented in this study suggest that α -diversity may not be a significant contributing factor to feed efficiency phenotypes in stable bacterial communities in growing beef steers. Previous studies have also observed the same relationships between rumen bacterial α -diversity and feed efficiency phenotypes in steers 12,13 . Other factors, such as divergences in individual taxa or functionality of the rumen microbiota, may play a greater role in dictation of host feed efficiency phenotypes.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies suggested correlations between rumen microbial groups and bovine feed efficiency traits (Carberry, Kenny, Han, McCabe, & Waters, 2012;Guan, Nkrumah, Basarab, & Moore, 2008;Hernandez-Sanabria et al, 2012). The relative proportion of sequences that were assigned to Prevotella appeared to be positively associated with high residual feed intake (RFI) in bulls, whereas an unidentified group within the order Bacteroidales was positively associated with low RFI in bulls (McCann et al, 2014). Lima et al (2015) have characterized the rumen fluid microbiomes of prepartum and postpartum high-producing Holstein cows and revealed that some bacteria have strong correlations with milk production.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has focused on characterization of the rumen microbiome among animals differing in feed efficiency (Jami et al, 2014;McCann et al, 2014). These studies characterized the bacterial community by sequencing 16S rRNA regions V1-V3 or V1/V3 individually.…”
Section: Introductionmentioning
confidence: 99%